ANALISIS ASPEK MORAL DALAM NOVEL JEJAK LANGKAH KARYA PRAMOEDYA ANANTA TOER - Tamba, Rolinca; Yunus, Syarifudin (Cahaya Ilmu Bangsa Institute, 2025)
The novel Jejak Langkah by Pramoedya Ananta Toer is a novel that contains strong moral values, especially those related to the struggle against oppression, freedom of thought, and social responsibility. Through the main character, Minke, he experiences significant moral development along with the socio-political dynamics that surround him. Through the characters and storyline, this novel shows how moral values ​​are shaped by life experiences, education, and awareness of injustice in colonial society. The moral aspect in the novel Jejak Langkah is very important because it describes the growth of character and the shift in values ​​experienced by the main character as a representation of the colonized people who are beginning to rise intellectually. The results of the analysis show that this work not only raises historical aspects, but also provides deep reflection on the importance of struggle, courage, justice, strong principles and a critical attitude towards power. Thus, Jejak Langkah becomes a literary work that not only has aesthetic value, but also educational value that is relevant in the context of character education.